Invariant Solutions and Conservation Laws of the (2 + 1)-Dimensional Boussinesq Equation - Wenjuan Rui; Peiyi Zhao; Yufeng Zhang (Abstract and Applied Analysis)
Invariant solutions and conservation laws of the (2 + 1)-dimensional Boussinesq equation are studied. The Lie symmetry approach is used to obtain the invariant solutions. Conservation laws for the underlying equation are derived by utilizing the new conservation theorem and the partial Lagrange approach.